Effects of lutein-phospholipids emulsion on oxidatively stressed egg yolk protein. (December 2021) - Yuan, Huchuan; Liu, Yu; Luo, Ruifeng; Qi, Zeliang; Qi, Haiwen; Du, Yuyu; Lu, Shiling; Dong, Juan; Wang, Qingling
Abstract: The oxidation of egg yolk protein may cause adverse effects on food during processing. In this study, lutein-phospholipids emulsion (LPE) was added to the hydroxyl radical oxidation system to investigate the effects of LPE on EYP. Changes in oxidation, protein structure and physicochemical properties of EYP were then characterized. Results showed that the total sulfhydryl content of EYP increased by 11.2 times while the carbonyl content of EYP decreased by 26.2 % in the oxidized group with 15 mL/L LPE compared with the oxidized group. Furthermore, the percentages of α -helix and β -sheet increased to 27.3 % and 24.5 % respectively, whereas the percentages of β -turn and random coil decreased to 27.7 % and 27.4 %. Moreover, the fluorescence intensity of EYP was increased with the increase in LPE ( P < 0.05). SDS-PAGE results showed that LPE decreased the oxidative aggregation degree of EYP. In terms of the physicochemical properties, addition of LPE improved the emulsion properties of EYP significantly ( P < 0.05), and increased the protein solubility by 134 %. The average particle size of EYP tended to decrease with the increase in LPE level. Collectively, these results show that LPE can inhibit oxidation and improve the physicochemical properties of EYP. Highlights: An innovative emulsion was made from lutein and egg yolk phospholipids. Lutein-phospholipids emulsion inhibited the oxidation of egg yolk protein. Lutein-phospholipids emulsion improved the emulsion capacity of egg yolk protein.